2000
DOI: 10.1590/s0074-02762000000200010
|View full text |Cite
|
Sign up to set email alerts
|

Canine experimental infection: intradermal inoculation of Leishmania infantum promastigotes

Abstract: Five mixed breed dogs were inoculated intradermally (ID)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
3
9
0
2
Order By: Relevance
“…6,[14][15][16][17] Previous studies showed that experimental IV infection was more likely to lead to overt disease than intradermal inoculation, which typically led to subclinical infection. 11,12,28 Our finding of small liver granulomas, an indication of an active cell mediated immune response, in the intradermally infected dogs is consistent with what was observed in resistant dogs naturally infected in endemic areas. [29][30][31] However, the previous work by Killick-Kendrick and others 10 showed development of severe disease (timing or nature not specified) in 48% of dogs infected intradermally with approximately 10 5 L. infantum promastigotes isolated from the mid guts of infected sand flies.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…6,[14][15][16][17] Previous studies showed that experimental IV infection was more likely to lead to overt disease than intradermal inoculation, which typically led to subclinical infection. 11,12,28 Our finding of small liver granulomas, an indication of an active cell mediated immune response, in the intradermally infected dogs is consistent with what was observed in resistant dogs naturally infected in endemic areas. [29][30][31] However, the previous work by Killick-Kendrick and others 10 showed development of severe disease (timing or nature not specified) in 48% of dogs infected intradermally with approximately 10 5 L. infantum promastigotes isolated from the mid guts of infected sand flies.…”
Section: Discussionsupporting
confidence: 87%
“…[3][4][5] Experimental infections of dogs have been carried out using a wide range of strategies that included the use of cultured promastigotes [6][7][8] or tissue-derived amastigotes. 6,7,9 Studies have used numbers of parasites that ranged from a few thousand to several million, delivered by the intradermal [10][11][12][13] or intravenous routes. 6,[14][15][16][17] Some of these inoculations included an extract of Lutzomyia longipalpis salivary glands in an unsuccessful attempt to increase parasite pathogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…Studies addressing the interaction between canine MØ and PMN are limited. In a previous study, our group showed that 3‐4 hours after dermal experimental inoculation promastigotes had already been internalized by PMN, proving the early involvement of these cells in dog infection . Recently, in an in vitro study, we proved that some parasites internalized by PMN maintained the viability and the replication ability, and thus the capacity to infect MØ.…”
Section: Discussionmentioning
confidence: 86%
“…Polymorphonuclear neutrophils (PMN) are the first cells to be recruited to the inoculation site, phagocytizing the parasite . Circulating monocytes infiltrate the canine dermis just a few hours after L infantum intradermal inoculation, where acquire the macrophage (MØ) functional phenotype.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation